Photocrosslinking polymeric ionic liquids via anthracene cycloaddition for organic electronics. Issue 32 (2nd August 2018) - Popere, Bhooshan C.; Sanoja, Gabriel E.; Thomas, Elayne M.; Schauser, Nicole S.; Jones, Seamus D.; Bartels, Joshua M.; Helgeson, Matthew E.; Chabinyc, Michael L.; Segalman, Rachel A.
Abstract : Polymeric ionic liquids are photocrosslinked without changing the ionic conductivity. This enables the simple processing necessary for fabrication of organic electronics. Abstract : Polymeric ionic liquids ( i.e., PILs) are single ion-conducting materials that exhibit the thermal and electrochemical stability of ionic liquids and the mechanical properties of polymers. Although PILs are exciting for a variety of applications in energy conversion and storage, the tradeoff between mechanics and ion transport remains an important limitation in materials design. Herein, a photocrosslinkable PIL based on the cycloaddition reaction of anthracene is converted from a viscous liquid into a soft solid without detrimental effects on the bulk ionic conductivity. The independent control of mechanical- and ion-conducting properties results from negligible changes in polymer segmental dynamics ( i.e., glass transition temperature) upon crosslinking. This was demonstrated for both a polymer ( i.e., N = 279) and its corresponding oligomer ( i.e., N = 10). The ease of processability facilitated by the presented molecular design is illustrated by both patterning the PIL into μm-sized features, and incorporating it as a dielectric in thin-film transistors for low-voltage operation independent of device fabrication geometry.